1995
DOI: 10.1007/bf02052444
|View full text |Cite
|
Sign up to set email alerts
|

Ileal pouch-anal anastomosis function following childbirth

Abstract: Incidence of pouch-related complications in patients with IPAA compares favorably with incidence in patients with ileostomy or Kock pouch. Operative rate for complications was 0 percent in IPAA patients compared with 9 percent in patients with ileostomy and 19 percent in patients with Kock pouch. The cesarean section rate was higher in patients with IPAA than in those with ileostomy or Kock pouch, and this may be caused by uncertainty about how to manage delivery in patients with IPAA. Pregnancy and childbirth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 12 publications
6
85
0
3
Order By: Relevance
“…17 Previous reports from the Mayo Clinic found that functional outcome after childbirth in women after IPAA was not compromised. 18 The present study confirms these earlier reports in a larger number of women with longer follow-up. A more complete understanding of delivery-related complications and functional outcomes awaits analysis.…”
Section: Discussionsupporting
confidence: 82%
“…17 Previous reports from the Mayo Clinic found that functional outcome after childbirth in women after IPAA was not compromised. 18 The present study confirms these earlier reports in a larger number of women with longer follow-up. A more complete understanding of delivery-related complications and functional outcomes awaits analysis.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike patients who have active disease at the plications in pregnancy. The most common side effects in this subset of patients during pregnancy are increased onset of pregnancy who remain active or worsen, patients with active ulcerative colitis who can be brought into stool frequency and incontinence, likely due to the pressure of the gravid uterus on the pelvic floor above the remission with aggressive drug therapy have an improved prognosis approaching that of patients whose disease was ileal pouch [26]. It is reasonable to anticipate a return to baseline pouch functioning postpartum.…”
Section: Effect Of Pregnancy On Inflammatory Bowel Diseasementioning
confidence: 99%
“…Furthermore, patients who have undergone ileal pouch-anal anastomosis surgery have higher rates of cesaCorticosteroids are also frequently used to control flares of IBD. Human studies have shown them to be rean section [26]. It is unclear, however, if the mode of delivery was altered in these patients out of necessity in well tolerated, with no significant increase in fetal complications as compared to the control population [2,14].…”
Section: Medical Treatment Of Ibd During Pregnancy and Lactationmentioning
confidence: 99%
“…Cesarean section should be recommended in CD patients with active perianal disease (45). In IBD patients with an ileoanal pouch studies have indicated that vaginal delivery after ileal pouch anal anastomosis (IPAA) is safe and not associated with long-term changes in pouch function (23,46,47). However, a study suggests that vaginal delivery increases the risk of sphincter muscle injury, which could have a long-term effect on pouch function (43).…”
Section: Discussionmentioning
confidence: 99%